Aplikasi Pesan Kamar Rumah Kost Kartika Berbasis Web Menggunakan Metode Waterfall - Irene Trivena Montalili; Abdul Rohman (Universitas Ngudi Waluyo, 2024)
Technology and information today is a human need in carrying out various activities. To make a booking transaction for Kartika's boarding room In this method there are 2 methods used, namely for program requirements and for Usability Testing Needs. The test results of the Functional Suitability Test on the Kartika Boarding House Information System Web-Based obtained the following results: Testing from Mrs. Kartika Boarding School Successfully Achieved 22/22 x 100% 100% Failed 0/22 x 100% 0% According to the results obtained through the Functional Suitability Test with If the percentage is 100%, then the Web-Based Kartika Boarding House Information System is declared